Smart cities get a boost from Galileo.
The vision of a smart transport system for cities has so far given rise to many technologies, from driverless cars to automatic detection of incidents and traffic light-free transportation designs. The GHOST consortium is contributing with a solution of its own : geo-localised snapshots of "Points of Interest' (POI) reporting the likes of street lighting anomalies or road deterioration.